Effects of Age of Rubber (Hevea brasiliensis Muell Arg.) Plantation on pH, Organic Carbon, Organic Matter, Nitrogen and Micronutrient Status of Ultisols in the Humid Forest Zone of Nigeria - Oku, Efﬁom; Iwara, Anthony; Ekukinam, Ekaette (Agriculture and Natural Resources, 2012)
Micronutrients are required by plants in minute quantities. Literature on the micronutrient status of soils sustaining rubber plantations in the humid forest zone of southern Nigeria is not readily available where a study was carried out on Ultisols to examine the status of manganese (Mn), iron (Fe), Copper (Cu) and zinc (Zn) in rubber plantations aged 7, 16, 39 and 41 yr. A grid sampling method was used to collect soil samples from ﬁ ve quadrats of 10 m × 10 m in each of the plantation plots. For each plot, ﬁ ve surface (0–15cm) soil samples were randomly collected and composited. The soil samples were analyzed for pH, organic carbon (OC), organic matter (OM), nitrogen (N), Mn, Fe, Cu and Zn. Data were analyzed using analysis of variance and Pearson’s correlation. The soils were strongly acidic (pH 4.0–4.4). The OC status was rated as very low (below 2%) in all the plantation soils. In addition, the OM was rated as low under the trees at 7, 16, and 39 yr whereas, for the 41 year-old plantation, it was rated as high. The Mn and Zn contents were rated as low for the 16, 39 and 41 year-old rubber plantations, whereas they were rated as medium under the 7 year-old rubber plantation. The Mn, Fe and Cu contents varied signiﬁ cantly (P < 0.01 to P < 0.05) with the age of trees, while Zn did not vary (P > 0.05) among the rubber plots. The fertility rating of Fe was toxic or excessive in all the plantations and the levels of Cu were rated high. The results showed that the contents of Zn, Fe, Cu and Mn in the soils decreased with increasing age of rubber plantation. The Mn content was rated as high, medium, medium and low in the 7, 16, 39 and 41 year-old plantations, respectively. The Fe contents were rated as high whereas the Cu contents were rated as medium. With the exception of the 7 year-old plantation, where Zn was rated as medium, the Zn contents were below the critical limits for crop production, with soils in the 16, 39 and 41 year-old rubber plantations beneﬁ ting from its application. The low values of soil pH across the rubber plantation plots did not signiﬁ cantly favour the increase in selected micronutrient levels in the soil. To improve the levels of micronutrients in the rubber plots, it is recommended that biomass burning should be discouraged during replanting as it strips the soil of these nutrients. The use of organo-mineral fertilizer combined with inorganic fertilizers is recommended. Care must be taken not to apply Mn in excess. A rubber-based agroforestry system, as opposed to rubber monocultures is recommended as it would improve the micronutrient levels of the soils in the plantation.